Teacher’s Strategy to Improve Children’s Cognitive through Outdoor Activities for Early Childhood - Istiqomah, Novia; Putro, Khamim Zarkasih (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
The researcher focused on the teacher’s strategy to improve children’s cognition through outdoor activities for early childhood, where the researchers aimed to find out how teachers learn about learning or outdoor activities, activities and preparation as well as the safety needed when doing outdoor activities for early childhood. The research method that the researcher uses is descriptive qualitative research. The data obtained from observations and interviews show similarities, namely outdoor activities stimulate children to develop more easily, children will be easier to understand and there is a real picture of what is explained. Outside they can feel the air, feel the opportunities of open space, and improve the ability to use muscles in new ways.